Effect of Pycnogenol Supplementation on Blood Pressure: A Systematic Review and Meta-analysis - Zheng ZHANG; Xing TONG; Yu-Lu WEI; Lin ZHAO; Jia-Ying XU; Li-Qiang QIN (Tehran University of Medical Sciences, 2018)
Background: Pycnogenol exhibits many biological activities, including control of blood pressure (BP). However, the reported results are inconsistent because of varied characteristics of participants and quality of studies. Thus, a meta-analysis was conducted to examine the effect of Pycnogenol supplementation on BP. Methods: This literature search of PubMed, the Web of Science and the Cochrane library was performed in May 2016 to identify eligible studies. Reference lists of the retrieved articles were also reviewed. Either a fixed-effects or, in the presence of heterogeneity, a random-effects model was used to calculate the effect of combined treatment. Results: We identified nine trials involving 549 participants who received Pycnogenol supplementation ranging from 150 mg/d to 200 mg/d. Compared with the control, the pooled estimate of change in systolic and diastolic BPs were -3.22 mmHg (95% CI: -6.20, -0.24) and -3.11 mmHg (95% CI: -4.60, -1.62), respectively. Subgroup analyses showed higher BP reduction among hypertensive participants or those who received intervention for more than 12 wk. However, this significant reduction was not observed in well-designed trials. Conclusion: This meta-analysis with nine trials provides better evidence that Pycnogenol exerts beneficial effects on BP.